2020
DOI: 10.3390/nano10122331
|View full text |Cite
|
Sign up to set email alerts
|

Porous Si/Fe2O3 Dual Network Anode for Lithium–Ion Battery Application

Abstract: Benefiting from ultra-high theoretical capacity, silicon (Si) is popular for use in energy storage fields as a Li–ion battery anode material because of its high-performance. However, a serious volume variation happens towards Si anodes in the lithiation/delithiation process, triggering the pulverization of Si and a fast decay in its capacity, which greatly limits its commercial application. In our study, a porous Si/Fe2O3 dual network anode was fabricated using the melt-spinning, ball-milling and dealloying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Two main morphologies, nanoparticles and nanosheets, can be easily d tected (Figure 2a and Figure S4a). Based on previous results [35], the nanosheets relate Fe2O3, while the nanoparticles correspond to Si. It was found that BM48-D4 contains Fe2 nanosheets and Si nanoparticles.…”
Section: Characterization Of Si/fe 2 O 3 /Rgomentioning
confidence: 71%
See 1 more Smart Citation
“…Two main morphologies, nanoparticles and nanosheets, can be easily d tected (Figure 2a and Figure S4a). Based on previous results [35], the nanosheets relate Fe2O3, while the nanoparticles correspond to Si. It was found that BM48-D4 contains Fe2 nanosheets and Si nanoparticles.…”
Section: Characterization Of Si/fe 2 O 3 /Rgomentioning
confidence: 71%
“…This was clearly lower than that of Si and Fe 2 O 3 (1007 mAh g −1 ) and limited the development of high-performance anodes. In our improved case, ball milling was utilized for melt-spinning ribbons prior to dealloying treatment [35]. As a result, a porous Si/Fe 2 O 3 dual network anode (free of Al 9 FeSi 3 ) was prepared by changing the elemental distribution and phase composition of the dealloying precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical properties of the NdFeO 3 and NdCoO 3 NFs as Li‐ion battery anodes were also researched. As presented in Figure 6A, for the first cycle, the broad peak at 0.07–0.1 V was attributed to the reaction of the NdFeO 3 electrode with the electrolyte and the development of a solid electrolyte interface film, where the peak at 1.85 V was mainly ascribed to the transition from Fe 2+ to Fe 3+ 48 . For the second cycle, the oxidation peak of the NdFeO 3 NFs moved slightly to 1.91 V, and the curve showed a wide peak at 0.42 V, whereas the broad peak from 0.6 to 1.0 V was due to the conversion of Fe 3+ to Fe 0 , 49 and the peak at 0.42 V could be derived from the valence changed of Nd.…”
Section: Resultsmentioning
confidence: 97%
“…The EIS diagram consists of a semicircle in the midhigh-frequency region and a diagonal line in the low-frequency region. Here, R CT in the mid-frequency region corresponds to the charge-transfer impedance and W O in the lowfrequency region corresponds to the diffusion of Li + inside the electrode material [56,57]. The R S and R CT values fitted from the equivalent circuit model are summarized in Table S3 for comparison.…”
Section: Lithium-ion Battery Performancementioning
confidence: 99%